Medical-surgical nursing - Ignatavicius, Donna D.; Workman, M. Linda (Elsevier, 2013)
Covers the trends, evidence-based treatment guidelines, and additional information needed for safe clinical practice in medical-surgical nursing. This book emphasizes on patient safety and NCLEX[registered] Examination preparation, ties to the QSEN priorities for patient safety, and a focus of clinical practice